2014
DOI: 10.1016/j.toxrep.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals in vegetables and fruits cultivated around the surroundings of Tummalapalle uranium mining site, Andhra Pradesh, India

Abstract: Vegetables (Tomato – Solanum lycopersicum, green chilli – Capsicum annum and bitter gourd – Momordica charantia) and fruits (Banana – Musa acuminata colla, papaya – Carica papaya and mosambi – Citrus limetta) from the cultivated areas around the Tummalapalle uranium mining site were analyzed for trace metals (Al, Cr, Mn, Fe, Ni, Cu, Zn, Pb, Be, V, Co, Cd and U) using inductively coupled plasma-mass spectrometer (ICP-MS). As per the estimated data, the concentrations of trace metals in vegetables and fruits are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 19 publications
4
30
3
1
Order By: Relevance
“…The EDI values for As, Pd, Cd and Hg were found to be 6.06 x 10 −4 , 1.14 x 10 −3 , 1.76 x 10 −4 and 1.08 x 10 −3 mg/day due to the consumption of 240 g/day of tomato, respectively, while the corresponding values due to the consumption of same amount of cabbage were 1.80 x 10 −3 , 2.37 x 10 −3 , 4.9 x 10 −4 and 1.33 x 10 −3 mg/day, respectively. The EDI of As, PB, Cd and Hg metals obtained due to the consumption of both cabbage and tomato were observed to be less than maximum tolerable daily intake of each metals as presented by Basha et al [76]; Shaheen et al [55] and Zheng et al [50] and indicated in Table 6. Likewise, the EDI of Zn, Cu, Fe, Mn, Cr, Ni and Co due to the consumption of tomato were found to be 7.69 x 10 −3 , 5.11 x 10 −3 , 2.67 x 10 −2 , 8.54 x 10 −3 , 4.68 x 10 −4 , 5.84 x 10 −4 and 1.98 x 10 −4 mg/day, respectively.…”
Section: Metalsmentioning
confidence: 77%
See 1 more Smart Citation
“…The EDI values for As, Pd, Cd and Hg were found to be 6.06 x 10 −4 , 1.14 x 10 −3 , 1.76 x 10 −4 and 1.08 x 10 −3 mg/day due to the consumption of 240 g/day of tomato, respectively, while the corresponding values due to the consumption of same amount of cabbage were 1.80 x 10 −3 , 2.37 x 10 −3 , 4.9 x 10 −4 and 1.33 x 10 −3 mg/day, respectively. The EDI of As, PB, Cd and Hg metals obtained due to the consumption of both cabbage and tomato were observed to be less than maximum tolerable daily intake of each metals as presented by Basha et al [76]; Shaheen et al [55] and Zheng et al [50] and indicated in Table 6. Likewise, the EDI of Zn, Cu, Fe, Mn, Cr, Ni and Co due to the consumption of tomato were found to be 7.69 x 10 −3 , 5.11 x 10 −3 , 2.67 x 10 −2 , 8.54 x 10 −3 , 4.68 x 10 −4 , 5.84 x 10 −4 and 1.98 x 10 −4 mg/day, respectively.…”
Section: Metalsmentioning
confidence: 77%
“…Estimated daily intake (mg/day/kg body weight) of toxic metals for adult population due to the consumption of contaminated vegetables in Mojo area, central Ethiopia. [50] c [76] https://doi.org/10.1371/journal.pone.0227883.t006…”
Section: Metalsmentioning
confidence: 99%
“…Kalagbor et al (2014) have studied the levels of heavy metals in four fruits from Nigeria. Basha et al (2014) have reported trace metals in vegetables and fruits cultivated in India. Igwegbe et al (2013) have reported a survey of heavy metal contents of selected fruit and vegetable crops in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of some elements like lead and cadmium can reduce mental and central nervous function and damage many organs. For this reason, a large number of studies have been undertaken to identify the potential risk factors with TTEs in different food matrices [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Abdrabo et al [11] have determined 23 elements in Spanish palm dates. Basha et al [4] have reported trace elements in vegetables and fruits cultivated in India. Taharn et al [12] have investigated the concentration of major to trace elements in tomato varieties economically grown in the northeast of Thailand.…”
Section: Introductionmentioning
confidence: 99%